2014
DOI: 10.1016/j.jacc.2014.07.937
|View full text |Cite
|
Sign up to set email alerts
|

Innervation Patterns May Limit Response to Endovascular Renal Denervation

Abstract: BACKGROUND Renal denervation is a new interventional approach to treat hypertension with variable results. OBJECTIVES The purpose of this study was to correlate response to endovascular radiofrequency ablation of renal arteries with nerve and ganglia distributions. We examined how renal neural network anatomy affected treatment efficacy. METHODS A multielectrode radiofrequency catheter (15 W/60 s) treated 8 renal arteries (group 1). Arteries and kidneys were harvested 7 days post-treatment. Renal norepinep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 22 publications
5
69
0
1
Order By: Relevance
“…[21][22][23] This study strongly suggests that renal sympathetic nerves attempt to regenerate but without apparent functional reconnection based on persistent NE level suppression. 14,[24][25][26] The high degree of distal nerve atrophy observed at 7 and 30 days in this study reported at chronic time points in other large animal experiments where RF ablation of renal nerves was performed. 14,20 It is necessary to further establish if the apparent morphological "recovery" of distal nerves could be responsible for the late increase in NE levels and whether this partial recovery may or may not produce a physiologic increase in blood pressure.…”
Section: Discussionsupporting
confidence: 57%
“…[21][22][23] This study strongly suggests that renal sympathetic nerves attempt to regenerate but without apparent functional reconnection based on persistent NE level suppression. 14,[24][25][26] The high degree of distal nerve atrophy observed at 7 and 30 days in this study reported at chronic time points in other large animal experiments where RF ablation of renal nerves was performed. 14,20 It is necessary to further establish if the apparent morphological "recovery" of distal nerves could be responsible for the late increase in NE levels and whether this partial recovery may or may not produce a physiologic increase in blood pressure.…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, the results of later animal studies cast doubts upon the lasting effect of catheter-based RDN when reinnervation was proved even after 5.5 months. 24 The total number of ablations 25 or even treatment locations 26 are discussed to improve the efficacy. However, evidence of the long-lasting effect of RDN, as well as evidence of better efficacy of multielectrode systems, is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The first study found that only 40% of the sympathetic fibers course within 2 mm from the lumen whereas 30% are found between 4 and 9 mm from the lumen [8], too far to be reached by low-energy radiofrequency ablation. The other study reported a segment-related distance from the lumen, with 75% of the sympathetic fibers situated within 3.4 mm from the lumen at the distal segment of renal arteries and within 9 mm from the renal artery wall at the proximal segment [9]. Further studies indicate that fibers in the renal artery branches are much more proximal to the lumen and perhaps more approachable by transcatheter techniques.…”
Section: Renal Nerve Anatomy and Clinical Implicationsmentioning
confidence: 99%